36-Month Evaluation of a Weight Management Programme in Chinese Overweight and Obese Adults - Yang, Xi; Chattopadhyay, Kaushik; Hubbard, Richard; Li, Jia-Lin; Li, Li; Lin, Yi (Frontiers in Public Health, 2021)
Background: Few comprehensive lifestyle intervention programmes have been investigated on overweight and obese adults in China. This study was to evaluate the effect of a 36-month weight management programme on weight loss and its maintenance among overweight and obese patients in Ningbo, China. Methods: Adults with BMI ≥24kg/m2 enrolled in this programme, including nutritional, physical activity, psychological and endocrinological counselling sessions, from July 2015 to January 2020. Adults participated in face-to-face counselling sessions and group-based education. Then, participants joined 21-day intensive programme using Bohe health APP and WeChat group to get personal advice of nutrition and lifestyle. In the end, participants were requested to join 33-month follow-ups including face-to-face counselling and personal advice on WeChat group. The main outcome was to evaluate the changes in weight at each followup from baseline weight. Results: In total, 692 adults participated in this entire weight management programme. During follow-ups, 579, 475, 299, 219, and 135 adults participated at 3, 6, 12, 24, and 36 months, respectively. All participants had a significant initial weight loss at 3 months, then maintained the weight loss during 33-month follow-ups. At 36 months, 11.0%, 6.4%, and 3.5% of all participants achieved 5%, 10%, and 15% weight loss from the baseline weight, respectively. Adjusted weight at 36 months was significantly reduced from the baseline weight in both sex (−7.2 kg). Conclusion: This weight management programme is suggested to benefit to reduce initial body weight and maintain long-term weight loss among overweight and obese adults.